Suez and After: Canada and British Policy in the Middle East, 1956–1960 - Cavell, Janice (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2007)
AbstractThe Suez crisis is generally considered to be a decisive turning-point in Canada’s relations with Great Britain. Prime Minister Louis St. Laurent and Secretary of State for External Affairs Lester Pearson refused to support Britain’s military action in Egypt, choosing instead to work through the United Nations for a resolution of the conflict. It seemed that Canada was repudiating a subservient role and declaring its final independence from the mother country. However, the documentary record shows that Canadian politicians and diplomats were in fact eager to work for what they believed to be Britain’s good. In their view, Britain had temporarily lost sight of its own, and the western world’s, best interests. During the years immediately after Suez, support for British policies was a priority of Canadian diplomats, most notably Arnold Smith, Canada’s ambassador to Egypt from 1958 to 1960. Smith played an important role in the resumption of diplomatic relations between Britain and Egypt. Drawing on previously unused documents in the files of the Department of External Affairs, this paper outlines Canadian views of, and Canada’s relationship to, British policy in the Middle East during and after Suez. It demonstrates that a “colony to nation” framework is inadequate for the study of the Anglo-Canadian relationship in the years following World War II. Instead, the broader context of Cold War politics must be taken into consideration. The paper also shows that despite the surface differences between Liberal and Conservative foreign policy, there were strong elements of continuity between the St. Laurent and Diefenbaker governments.